IMPLEMENTASI KURIKULUM MERDEKA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Rizki Agustina; Fajri Ismail; Muhammad Win Afgani (CV. ADIBA AISHA AMIRA, 2023)
The Merdeka Curriculum is an idea from the Minister of Education and Culture of the Republic of Indonesia, namely Nadiem Makarim which he delivered in a speech commemorating National Teacher's Day on November 25 2019. Nadiem stated that the Merdeka Curriculum is an atmosphere in which schools, teachers and students have the freedom to innovate and learn independently and creatively. This paper uses the library research method by critically and in-depth review of relevant library materials such as books and journals that are worthy of being used as references in the preparation of this paper. The data collection technique used in this paper uses secondary data, namely by collecting data indirectly by examining the object in question. This paper aims to describe and examine more deeply the Merdeka Curriculum and learning achievements in Islamic religious education.